2003
DOI: 10.1093/emboj/cdg391
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase stabilization at stalled replication forks requires Mec1 and the RecQ helicase Sgs1

Abstract: To ensure proper replication and segregation of the genome, eukaryotic cells have evolved surveillance systems that monitor and react to impaired replication fork progression. In budding yeast, the intra-S phase checkpoint responds to stalled replication forks by downregulating late-®ring origins, preventing spindle elongation and allowing ef®cient resumption of DNA synthesis after recovery from stress. Mutations in this pathway lead to high levels of genomic instability, particularly in the presence of DNA da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
324
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 310 publications
(344 citation statements)
references
References 55 publications
(102 reference statements)
18
324
1
1
Order By: Relevance
“…3A,B). Consistent with previous data, ChIP experiments in cells synchronized by ␣-factor and released into HU demonstrated that Pol -HA was enriched at early origins (Aparicio et al 1999;Cobb et al 2003;Katou et al 2003;Lucca et al 2004). As expected, Pol -HA was not enriched in wild-type cells at sequences 14 kb from ARS607 or 8 kb from the ARS 305, indicating that HU had stalled forks before they reached distal positions.…”
Section: Stalled Replisomes Are Unstable In Asf1⌬ Cellssupporting
confidence: 90%
See 4 more Smart Citations
“…3A,B). Consistent with previous data, ChIP experiments in cells synchronized by ␣-factor and released into HU demonstrated that Pol -HA was enriched at early origins (Aparicio et al 1999;Cobb et al 2003;Katou et al 2003;Lucca et al 2004). As expected, Pol -HA was not enriched in wild-type cells at sequences 14 kb from ARS607 or 8 kb from the ARS 305, indicating that HU had stalled forks before they reached distal positions.…”
Section: Stalled Replisomes Are Unstable In Asf1⌬ Cellssupporting
confidence: 90%
“…The S-phase checkpoint allows cells to survive in the presence of replication stress by maintaining the stability of replisome proteins at stalled replication forks (Cobb et al 2003;Katou et al 2003;Tercero et al 2003;Lucca et al 2004). Because asf1⌬ cells display spontaneous DNA damage phenotypes (see introduction), and because Asf1 is required to complete DNA synthesis in the presence of DNA damage (Fig.…”
Section: Stalled Replisomes Are Unstable In Asf1⌬ Cellsmentioning
confidence: 99%
See 3 more Smart Citations